APPROACHES FOR TEACHING UZBEK AS A NATIVE TONGUE - Abduvaliyeva , Ziyoda (Educational Research in Universal Sciences, 2023)
This article discusses that Students’ professional development through the use of interactive methods involves the development of critical thinking, which implies a flexible, autonomous, and significant stance. Because it makes learning more self-aware and reflective and develops a person’s capacity for communication, this approach greatly raises the validity of education.